A novel epigenetic CREB‐miR‐373 axis mediates ZIP4‐induced pancreatic cancer growth. Issue 9 (16th July 2013) - Zhang, Yuqing; Yang, Jingxuan; Cui, Xiaobo; Chen, Yong; Zhu, Vivian F.; Hagan, John P.; Wang, Huamin; Yu, Xianjun; Hodges, Sally E.; Fang, Jing; Chiao, Paul J.; Logsdon, Craig D.; et al.
<x xml:space="preserve">Abstract</x> Changes in the intracellular levels of the essential micronutrient zinc have been implicated in multiple diseases including pancreatic cancer; however, the molecular mechanism is poorly understood. Here, we report a novel mechanism where increased zinc mediated by the zinc importer ZIP4 transcriptionally induces miR‐373 in pancreatic cancer to promote tumour growth. Reporter, expression and chromatin immunoprecipitation assays demonstrate that ZIP4 activates the zinc‐dependent transcription factor CREB and requires this transcription factor to increase miR‐373 expression through the regulation of its promoter. miR‐373 induction is necessary for efficient ZIP4‐dependent enhancement of cell proliferation, invasion, and tumour growth. Further analysis of miR‐373 in vivo oncogenic function reveals that it is mediated through its negative regulation of TP53INP1, LATS2 and CD44. These results define a novel ZIP4‐CREB‐miR‐373 signalling axis promoting pancreatic cancer growth, providing mechanistic insights explaining in part how a zinc transporter functions in cancer cells and may have broader implications as inappropriate regulation of intracellular zinc levels plays an important role in many other diseases.